KONSEP DAN AKTUALISASI KERUKUNAN ANTAR UMAT BERAGAMA DI MADRASAH ALIYAH NEGERI 2 HALMAHERA UTARA - Usman, Harianto; Saban, Mariana (EDUKASI, 2022)
Inter-religious harmony is a real problem for all time. Inter-religious harmony gots high attention to the importance since the beginning of the development of Islam, both stated in the Qur'an and implied in various behaviors of the Prophet Muhammad SAW. The concept of religious harmony has been applied at Madrasah Aliyah Negeri 2 Halmahera Utara due the school has students with different various religion background.Ã‚Â  The understanding of the right to freedom of religion within the school environment, both between teachers and students as well as students in this school is a shared responsibility, and we live this condition with a full sense of togetherness, harmony and form of service from teachers to students of other religions. Treated the same as Muslim students. This condition is seen as very important to be implemented, maintained and maintained for its sustainability